Efficacy of peritoneal dialysis in the treatment of refractory heart failure - J.Emilio Sánchez; Carmen Rodríguez; Elena Astudillo; José Joaquín Bande (RDPLF, 2018)
Heart failure (HF) is a progressive disorder even with adequate treatment. Fluid removal may aid in the management of these patients. We evaluated the efficacy of peritoneal dialysis (PD) in the treatment of refractory HF. Patients and Methods : Prospective, non-randomized study involving patients with congestive HF refractory to maximun tolerable drug treatment. All of them were treated with PD. We analysed clinical data and functional status. To determine efficacy we compared the perceived state of health to PD patients respect to those reported with conservative therapies. Finally, we carried out a cost-utility evaluation. Results : Seventy-eight patients (68% men, 66±10 years) were included and 14 were still undergoing PD at the end of the follow-up period (22±9 months). Seventy patients underwent only one daily nocturnal exchange; the rest, 2 or 3 exchanges according to different degrees of renal failure. All of them improved their NYHA functional status, (4% three classes, 63% two, 33% one; p<0.001), with a reduction in their pulmonary artery systolic pressure (48±13 vs 28±10 mmHg; p=0.007). Hospitalization rates underwent a dramatic reduction (from 63±16 to 9±7 days/patient/year; p=0.002). Life expectancy on PD was 88% after 12 months of treatment, and 72% and 54% after 18 and 24 months. PD was associated with a perceived state of health higher than with conservative therapy, (0,416±0,218 vs 0, 658±0,114, p <0.02 ). PD is cost-effective compared with the diuretic regimens. Conclusions : PD is a good option for patients with refractory HF; it improves the functional status and quality of life, reduces morbidity, mortality and health care costs.